Harmonization of National Law and Global Trade Standards in International Business Transactions - Aurora Fatya Jenar; Wafda Vivid Izziyana (PT Justitia Legal Research, 2026)
This study analyzes the alignment between national legal frameworks and global trade standards in the context of international business transactions. The research identifies the growing importance of regulatory consistency as countries integrate more deeply into global markets. The study employs a qualitative descriptive approach supported by document analysis to examine legal structures, trade instruments, and institutional mechanisms that influence harmonization. Findings indicate that national regulations have increasingly adapted to global trade norms, particularly in areas related to tariff systems, customs procedures, product quality standards, and dispute settlement mechanisms. This alignment strengthens legal certainty for businesses and enhances access to international markets. The analysis further shows that harmonization contributes to more efficient supply chain management, reduces transaction costs, and improves product competitiveness. Evidence reveals uneven adaptation across sectors, showing that industries already engaged in global markets adjust more rapidly than those focused on domestic production. The study identifies challenges related to regulatory complexity, institutional coordination, and readiness among domestic industries. These challenges require systematic policy reform, institutional synergy, and continuous engagement with international organizations. The research concludes that harmonization is not only a legal adjustment process but also a strategic economic instrument that strengthens national competitiveness in the global trading system. The process creates a more predictable business environment, enhances the credibility of national products, and supports sustainable economic development through deeper integration with global markets.